(untitled) (Verba Vitae Unwira, 2020)
Political economy is a study area that deals with the distribution of power and economic resources. Contemporary media with a convergent, digitalized, multiplatform and internet-based character indicates a more complex, multidisciplinary, and even transdisciplinary reflection of political economy. This paper is a literature review for an introduction to the study of contemporary media political economy with a feminist perspective. As the metamorphosis of media from mass to convergence and digital, this paper will discuss the feminist political economy in the context of mass media towards cyber media feminism. This literature study found 3 urgent things that should be the focus of the study of Political Economy of Feminist Media and Cyberfeminism in the context of communication science studies, namely: 1) Feminist studies are placed as part of the critical tradition of communication theory. This approach examines how communication praxis propagates gender ideology. Feminist studies as one of the five current perspectives of political economy of media are oriented towards emancipation praxis, 2) The definition of technology has a male bias because it is an emphasis on technology dominated by men who conspire to reduce the importance of women’s technology. The trend of cyber technology that looks pro-women must still be sharpened critically to male domination through discourse to give birth to symbolic violence - violence that is accepted because of ignorance, and 3) A political movement, feminism, and cyber feminism must be able to manifest proof of promises. Manifested by mainstreaming counter-discourse ideas in public spaces.